Pendampingan Ibu Hamil Kekurangan Energik Kronik (KEK) untuk Penurunan Angka Stunting di Desa Pacellekang - Armiyanti Nur; Siti Komariah; Aulia Furkania (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2020)
Monitoring nutrition and health during the First 1000 Days of Life (HPK) in Pacellekang Village is very important to prevent stunting. However, during the pandemic, many posyandu were forced to stop their activities because they were in the red zone. The assistance program for malnourished pregnant women (KEK) aims to improve the health and nutritional status of KEK pregnant women in Makassar City. Community service activities are carried out online using Zoom meetings, WhatsApp groups and Google Forms. The results of the service show that most of the knowledge and attitudes of pregnant women regarding nutrition and health are classified as good. The majority (85.2%) of pregnant women had carried out pregnancy checks at least four times with a midwife or doctor during pregnancy. Apart from that, 88.9% of pregnant women regularly take blood supplement tablets. Around 85.2% of pregnant women follow the principles of balanced nutrition in their daily diet. However, 55.6% of pregnant women who frequently experience nausea and vomiting tend to lose their appetite and skip meals and snacks. Based on program monitoring in October, there were records that two pregnant women were unable to provide exclusive breastfeeding (IMD) due to premature birth (separation care), and young mothers (under 20 years) felt anxious when breast milk did not come immediately after delivery, so they gave Formula milk.